Cross-Cultural Adaptation, Reliability, and Validity of the Turkish Version of the Compliance Questionnaire on Rheumatology in Patients With Behçet's Disease. (September 2016) - Cinar, Fatma Ilknur; Cinar, Muhammet; Yilmaz, Sedat; Acikel, Cengizhan; Erdem, Hakan; Pay, Salih; Simsek, Ismail
Purpose: The aim of this study was to examine the psychometric properties of the Turkish versionof the Compliance Questionnaire on Rheumatology (CQR-T) for patients with Behçet's disease (BD).Method: A sample of 105 Turkish patients with BD participated in this study. The scale was cross-culturally adapted through a process including translation, comparison with versions in other languages, back translation, and pretesting. Construct validity was evaluated by factor analysis, and criterion validity was evaluated using the Morisky Medication Adherence Scale.Results: The CQR-T demonstrated acceptable internal consistency (Cronbach's α = .832), adequate test–retest reliability (intraclass correlation coefficient = .630), and correlations with Morisky Medication Adherence Scale scores ( r = −.389, p < .001), indicating convergent validity.Conclusion: The CQR-T was found to be a valid and reliable instrument for evaluating the compliance of Turkish BD patients with prescribed medications.Implications for Practice: The CQR-T might be a helpful tool in two ways: for determining the level of compliance of patients with BD and for adjusting their management and follow-up based on the results.